HYGIENIC ASSESSMENT OF VEGETABLE FOOD SAFETY IN CONDITIONS OF THE APPLICATION OF FUNGICIDE BASED ON THE NEW COMPOUND AMETOCTRADIN - S.V. Bilous (Bogomolets National Medical University, 2016)
A wide range of pesticides, as well as double or triple fungicides application during the crops growing season pose a real threat or potential impact of these pesticides on humans due to its accumulation in agricultural raw materials. Ametoctradin (a new active substance of Orvego, SC, preparation, BASF SE, Germany) recently been synthesized among the derivatives of triazolopyrimidines with high fungicidal activity, but its toxicological and hygienic assessment is still not performed in Ukraine. The aim of the study was hygienic assessment of vegetable food safety in conditions of Orvego SC application and substantiation of hygienic standards for it in onions, potatoes, cucumbers and tomatoes to preserve the health for consumers of these products. The samples of studied vegetables had been sampling from the date of treatment and dates with specified intervals throughout the growing season. Determination of ametoctradin residual amounts was carried out by approved guidelines using high performance liquid chromatography. Calculations of the pesticide destruction rate constant (K), half-life period (t50) 95% and 99% destruction rates (t95) (t99) were performed using Excel (version 14.0.6023.1000, 2010) software on PC. The dynamics of ametoctradin content in vegetable products was studied. Mathematical modeling of the test compound destruction processes in vegetables revealed that ametoctradin half-life ($ 50 days) in onions is 9.8, the potato - 7.1, the cucumbers - 6.9 and in tomatoes - 6.2. There is no significant differences in the rate of ametoctradin destruction in the studied vegetables (p <0.05). Taking into account the findings, the $ 50 average value in vegetable products equal to 7,5 ± 0,7 days was calculated, allowing us to pertain ametoctradin to the 3 class of hazard (moderately hazardous compounds by persistence in plants). It was proved that in the real conditions of agricultural sector of Ukraine using traditional technical means, respecting the established farming and hygiene regulations application of Orvego, SC fungicide to protect vegetables is not a dangerous factor to public health from the nutritional hygiene point of view.